Detection of CTC Clusters and a Dedifferentiated RNA‐Expression Survival Signature in Prostate Cancer. Issue 2 (15th November 2018) - Kozminsky, Molly; Fouladdel, Shamileh; Chung, Jae‐Seung; Wang, Yugang; Smith, David C.; Alva, Ajjai; Azizi, Ebrahim; Morgan, Todd; Nagrath, Sunitha
Abstract: Rates of progression and treatment response in advanced prostate cancer are highly variable, necessitating non‐invasive methods to assess the molecular characteristics of these tumors in real time. The unique potential of circulating tumor cells (CTCs) to serve as a clinically useful liquid biomarker is due to their ability to inform via both enumeration and RNA expression. A microfluidic graphene oxide‐based device (GO Chip) is used to isolate CTCs and CTC clusters from the whole blood of 41 men with metastatic castration‐resistant prostate cancer. Additionally, the expression of 96 genes of interest is determined by RT‐qPCR. Multivariate analyses are conducted to determine the genes most closely associated with overall survival, PSA progression, and radioclinical progression. A preliminary signature, comprising high expression of stemness genes and low expression of epithelial and mesenchymal genes, potentially implicates an undifferentiated CTC phenotype as a marker of poor prognosis in this setting. Abstract : A microfluidic graphene oxide‐based device (GO Chip) is used to isolate circulating tumor cells (CTCs) and CTC clusters from the whole blood of 41 metastatic castration‐resistant prostate cancer patients. A preliminary RNA signature, comprising high expression of stemness genes and low expression of epithelial and mesenchymal genes, potentially implicates an undifferentiated CTC phenotype as a marker of poor prognosis.